Pulse Train from Graphene Solutions - Wang, Jin; Shu, Cheng; Fu, Lili; Liu, Chunxiao; Zhou, Yan; Wei, Wei; Peng, Bo (Asian Journal of Chemistry, 2012)
We report on pulse train generation in an erbium-doped fiber laser with atomic layer graphene-water solutions which are fabricated from graphite by wet-chemistry techniques. Pulse trains generated from various concentration of graphene-water solutions are investigated under different laser energy. Present results show that atomic layer graphene-water solutions could be a promising saturable absorber for pulse trains due to its wavelength-independent ultrafast saturable absorption, good processbility and low cost.